Dietary restraint as a mediator : investigating weight changes up to 9 years - Salmela, Jutta (2021)
It has been shown that type 2 diabetes (T2DM) is preventable by changing lifestyle. However, studies have rarely examined the behavioral mechanisms through which lifestyle interventions influence T2DM risk factors, particularly body weight. In this study we were interested in investigating whether eating behavior (restrained eating with flexible and rigid dimensions, disinhibition and susceptibility to hunger) and body weight changed differently in lifestyle intervention and control groups during the 9-year study period. We also examined whether changes in eating behavior during the first year mediated the effects of the intervention on body weight change or T2DM incidence during a period of 9-years from baseline. Overweight, middle-aged participants (38 men and 60 women) with impaired glucose tolerance in the Kuopio research center of the Diabetes Prevention Study (DPS) were randomized to an intensive, individualized lifestyle intervention group (median duration 5 years) or a control group. At baseline and annually thereafter participants completed Three Factor Eating Questionnaire (TFEQ), had 75-g oral glucose tolerance test and their body weight was measured. During the first year of the study restrained eating (p<0.001), flexible (p=0.018) and rigid restraint (p=0.001) increased, and body weight decreased (p<0.001) more in DPS intervention group compared to control group and the difference remained regarding restrained eating (p=0.002), rigid restraint (p=0.004) and weight loss (p=0.046) up to 9-years. Mediation analyses revealed that the first year increases in dietary restraint (restrained eating, flexible and rigid restraint) mediated the impact of the DPS intervention on weight loss during the 9 years from baseline. Our findings suggest that intensive lifestyle intervention has long-lasting effects on dietary restraint and body weight. The mediation analyses suggested that especially early phase increase in dietary restraint may be one essential lifestyle change influencing weight reduction even up to 9 years.